Menggapai Permainan Tradisional Anak Indonesia dalam Perangkat Berbasis Android - Handayani, Sri (Universitas Semarang, 2016)
Play is a child's world, by playing the child will learn to interact, learn to share, emotion and hone motor skills that support the development of the child. Game in the era of information technology is a game that does not require a lot of movement and tend to release attachment to the neighborhood children and their parents. While traditional games children Indonesia offered Android-based devices today is still an application to introduce the history of the game and how to play. This app only provides information, has not been able to replace the benefits and functions of traditional games of Indonesian children the truth.Indonesian traditional games children a heritage, a legacy of the ancestors of Indonesia. So as to preserve the cultural ancestry as means of Indonesian children were able to preserve the culture of Indonesia. But now it has changed the cultural inheritance child's play. Culture plays a passive child, and let go of attachment to the child with the parents and the environment.The biggest challenge will be faced in the future is how to implement actual meaning for children to play in Android-based devices.